Computer-aided approach for the development and characterization of bioplastic from orange peels incorporated with rice husk - Nurul Syafiqah Ismail (2022)
Nowadays, people use plastic bags as packaging materials because it is lightweight, cheap, and convenient. However, the use of petroleum-based plastics can have a major environmental impact. Based on statistical data obtained from the Solid Waste and Public Cleansing Management Corporation (SWCorp), the daily waste production among Malaysians increased by 100.75 percent to 38,142 tons in 2018, compared to 19,000 tons, in 2005. This research focuses on developing and characterizing pectin and cellulose-based bioplastic formulation. Development of pectin and cellulose-based bioplastic was carried out at difference ratio pectin and cellulose (6:4, 7:3, 8:2, 9:1) % and mass of plasticizer (0.1, 0.2, 0.3, 0.4) ml/g whereas cellulose dissolved in a 3% (w/v) of NaOH, and pectin dissolved in distilled water with pectin distilled water = 1:10 (w/v) ratio. The films were prepared by casting technique using a film-formation solution. In order to obtain the optimal condition in developing the bioplastic, an optimization process has been carried out. A Central Composite Design (CCD) technique from Response Surface Methodology (RSM) was used to investigate the effects of independent variables on bioplastic developed properties. Moisture content, thickness, and density of bioplastic developed were analyzed. From the analysis of experimental results, the highest and lowest value of moisture content (39.98% and 6.84%), film thickness (0.232 mm and 0.040 mm), and film density (0.049 g/ml and 0.027 g/ml) was obtained, respectively. The coefficient of determination (R2) for moisture content. film thickness, and film density was 0.8568, 0.9473, and 0.7296, respectively. The optimized condition for production bioplastic was 6.001% concentration pectin, 0.408 g of plasticizer, and 26.184 ml volume film-formation solution with a high value of desirability (1.000), which was giving film with moisture content 41.654%, film thickness 0.230 mm. and film density 0.049 g/ml.